COVID‐19‐associated immune‐mediated encephalitis mimicking acute‐onset Creutzfeldt‐Jakob disease. Issue 12 (26th November 2021) - Beretta, Simone; Stabile, Andrea; Balducci, Claudia; DiFrancesco, Jacopo C.; Patruno, Adriana; Rona, Roberto; Bombino, Michela; Capraro, Cristina; Andreetta, Francesca; Cavalcante, Paola; Moda, Fabio; Citerio, Giuseppe; et al.
Abstract: We report a subtype of immune‐mediated encephalitis associated with COVID‐19, which closely mimics acute‐onset sporadic Creutzfeldt–Jakob disease. A 64‐year‐old man presented with confusion, aphasia, myoclonus, and a silent interstitial pneumonia. He tested positive for SARS‐CoV‐2. Cognition and myoclonus rapidly deteriorated, EEG evolved to generalized periodic discharges and brain MRI showed multiple cortical DWI hyperintensities. CSF analysis was normal, except for a positive 14‐3‐3 protein. RT‐QuIC analysis was negative. High levels of pro‐inflammatory cytokines were present in the CSF and serum. Treatment with steroids and intravenous immunoglobulins produced EEG and clinical improvement, with a good neurological outcome at a 6‐month follow‐up.